2022
DOI: 10.3390/cancers14112718
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Approaches and Outcome of Patients with Neuroendocrine Neoplasia Grade 3 in German Real-World Clinical Practice

Abstract: Background: Neuroendocrine neoplasia grade 3 (NEN G3) represents a rare and heterogeneous cancer type with a poor prognosis. The aim of our study was to analyze real-world data from the German NET Registry with a focus on therapeutic and prognostic aspects. Methods: NEN G3 patients were identified within the German NET Registry. Demographic data and data on treatments and outcomes were retrieved. Univariate analyses were performed using the Kaplan–Meier-method. Multivariate analysis was performed using a Cox p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Given that some of these neoplasms share similar immunohistochemical characteristics with small cell lung cancer (SCLC), chemotherapy of etoposide-platinum (EP), the standard of care for SCLC, is widely used in gastroenteropancreatic NECs (GEP-NECs) ( 7 , 8 ). Several retrospective studies evaluated the efficacy of EP as first-line chemotherapy in GEP-NECs and found a median response rate of 42.95% (28–62.5%), a median progression-free survival (PFS) of 5.65 months and a median OS of 11.67 months ( 9 - 11 ). However, according to National Comprehensive Cancer Network (NCCN) guidelines ( 12 ), the recommendation for EP regimen in GEP-NECs is only grouped into category 2A, which means the adoption of this regimen was based upon only low-level evidence, indicating that there is a lack of optimal treatment regimen for GEP-NECs.…”
Section: Introductionmentioning
confidence: 99%
“…Given that some of these neoplasms share similar immunohistochemical characteristics with small cell lung cancer (SCLC), chemotherapy of etoposide-platinum (EP), the standard of care for SCLC, is widely used in gastroenteropancreatic NECs (GEP-NECs) ( 7 , 8 ). Several retrospective studies evaluated the efficacy of EP as first-line chemotherapy in GEP-NECs and found a median response rate of 42.95% (28–62.5%), a median progression-free survival (PFS) of 5.65 months and a median OS of 11.67 months ( 9 - 11 ). However, according to National Comprehensive Cancer Network (NCCN) guidelines ( 12 ), the recommendation for EP regimen in GEP-NECs is only grouped into category 2A, which means the adoption of this regimen was based upon only low-level evidence, indicating that there is a lack of optimal treatment regimen for GEP-NECs.…”
Section: Introductionmentioning
confidence: 99%
“…Published data from Germany and other European countries have often focused on retrospective analysis of oncological studies, 19 mostly obtained from referral centers, or the analysis of specific subgroups. 20,21 Due to national restrictions and data protection rules, large population-based data such as provided by the Surveillance, Epidemiology, and End Results (SEER) Program in the United States 5,22 are often not available for Europe. In particular, regarding the more recent changes in the WHO and TNM classifications, population-based incidence data are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Uncertainty exists whether the observed increase in NEN incidence is due to improved detection strategies of these tumors, altering risk factors, or changes in tumor biology. Published data from Germany and other European countries have often focused on retrospective analysis of oncological studies, 19 mostly obtained from referral centers, or the analysis of specific subgroups 20,21 . Due to national restrictions and data protection rules, large population‐based data such as provided by the Surveillance, Epidemiology, and End Results (SEER) Program in the United States 5,22 are often not available for Europe.…”
Section: Introductionmentioning
confidence: 99%